External Supervision System Reform In The State Of The Republic Of Indonesia - Gusman, Delfina Gusman; Nazmi, Didi Nazmi (Faculty of Law, Universitas Jenderal Soedirman, 2023)
The revelation of the engineering handling of the death case of Police Brigadier Nofriansyah Yosua Hutabarat has had an impact on raising other issues related to unprofessionalism within the Indonesian National Police such as the issue of the 303 gambling consortium, drugs, promotions associated with factions within the POLRI, luxury lifestyle, case transactions and so on The public considers that unprofessionalism within the Indonesian National Police does not only occur with individual members of the police but is already